The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/1538574413503563
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Arteritis Presenting as Critical Lower Limb Ischemia

Abstract: A 62-year-old woman presented with ischemic pain of her lower limb on 2 occasions, without upper limb or cranial vessel involvement. She was treated with open bypass of her left lower limb when she presented with critical limb ischemia during her second admission. Although bilateral temporal artery biopsies were negative, superficial femoral artery biopsy at the time of surgery confirmed the diagnosis of giant cell arteritis. Corticosteroid therapy was promptly commenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…El inicio precoz de terapia con corticoides es fundamental para evitar progresión de la enfermedad que puede llegar a comprometer la viabilidad de la extremidad, con una respuesta clínica rápida en etapas agudas 12 . En esta paciente dado la recaída de su enfermedad sitémica al bajar la dosis de esteroides, el tratamiento con Tocilizumab permitió la remisión mantenida de la vasculitis y fue útil para bajar la dosis de esteroides, evitando sus complicaciones.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El inicio precoz de terapia con corticoides es fundamental para evitar progresión de la enfermedad que puede llegar a comprometer la viabilidad de la extremidad, con una respuesta clínica rápida en etapas agudas 12 . En esta paciente dado la recaída de su enfermedad sitémica al bajar la dosis de esteroides, el tratamiento con Tocilizumab permitió la remisión mantenida de la vasculitis y fue útil para bajar la dosis de esteroides, evitando sus complicaciones.…”
Section: Discussionunclassified
“…El tratamiento quirúrgico con puentes arteriales ha presentado alta tasa de oclusión precoz 12 . Se ha descrito angioplastia con balón como terapia adyuvante al pulso de corticoides logrando tasas de permeabilidad primaria y secundaria de 65,2 y 89,7% respectivamente 14 .…”
Section: Discussionunclassified
“… 2 , 12 In our review, patients have been shown to develop ischemic complications after initiation of steroid therapy. 4 , 8 , 9 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…In a series of 10 patients, Both et al demonstrated a 100% resolution of stenosis following angioplasty; however, 50% had developed restenosis on 5 months' followup (35). Loo et al demonstrated variable surgical success rates from 60% to 100% (36).…”
Section: Vasculitismentioning
confidence: 97%